UJI AKTIVITAS ANTIOKSIDAN KULIT BUAH TIGA KULTIVAR DELIMA (PUNICA GRANATUM L.) DAN ISOLASI SENYAWA AKTIF DARI KULTIVAR TERPILIH - Filamenti Heryadi, Reckta
Antioxidants are chemical compound that can interact and neutralize free radicals. They donate electrons to free radicals which prevent the reaction. Based on research, source of antioxidant is pomegranate peel. Nowadays in Indonesia there are three cultivar of pomegranate which depend on the peel skin i.e white, black and red. The objectives of this research is to study antioxidant activity of three cultivar of pomegranate peel by determination of IC50 scavenging free radicals activity DPPH and isolation antioxidant compound and determine the active compound, determine fenolic and flavonoid total content and correlation of phytochemical profile with antioxidant activity. Crude drugs of pomegranate peels are extracted by reflux method and etanol as a solvent. All of three extract are continue fractionation by liquid-liquid extraction. All of extract and fraction pomegranate peels are determined IC50 scavenging free radicals activity DPPH, fenolic and flavonoid total content. Ethyl acetate fraction of black pomegranate was sub fractioned using VLC (Vacuum Liquid Chromatography). Sub fraction 11 and 12 was purified using TLC preparative. The purity was observed using single development of TLC and two dimensional TLC. Isolate was characterized using specific spot reagent (FeCl3 5% and sitroborat), ammonia fume, two dimensional thin paper chromatography and TLC densitometer. Extract black pomegranate gave the highest of IC50 scavenging free radicals activity DPPH, fenol and flavonoid total content respectively were 1,52±0,10 ?g/mL, 70,60 ± 0,41 g GAE/100 g, 10,89 ± 0,11 g QE/100 g. The highest IC50 scavenging free radicals activity DPPH in ethyl acetate and water fraction black pomegranate was 0,75 ± 0,04 ?g/mL and 0,75 ± 0,02 ?g/mL. Fenolic and flavonoid total content was higher in water fraction of black pomegranate respectively 96,40 ± 0,49 g GAE/100 g, 11,96 ± 0,20 g QE/100 g. Dominant fraction was obtained from fraction 12 that predicted to be flavonol and isolate was obtained from fraction 11. Isolate was predicted to be flavonol 7-O monoglycose with or without a free 5-OH.